1985
DOI: 10.1152/ajprenal.1985.248.2.f233
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid activation of Na+/H+ exchange in renal brush border vesicles: kinetic effects

Abstract: Administration of the synthetic glucocorticoid dexamethasone to adrenalectomized rats increased Na+/H+ exchange activity in isolated renal brush border membrane vesicles. Treatment altered the initial rate of Na+ uptake by increasing Vmax (19.90 +/- 2.17 vs. 27.32 +/- 1.50 nmol.mg protein-1.5 s-1) and not the apparent affinity KNa+ (8.33 +/- 1.11 vs. 7.94 +/- 1.60 mM). Dexamethasone treatment resulted in a proportional increase in 1 mM Na+ uptake at every intravesicular pH measured. When these data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
4
13
0
1
Order By: Relevance
“…Glucocorticoids increase proximal tubule apical membrane Na/H antiporter activity in vivo and in cell culture (5,9,17). The present studies also demonstrate that glucocorticoids increase NHE3 protein abundance.…”
Section: Discussionsupporting
confidence: 73%
“…Glucocorticoids increase proximal tubule apical membrane Na/H antiporter activity in vivo and in cell culture (5,9,17). The present studies also demonstrate that glucocorticoids increase NHE3 protein abundance.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, glucocorticoids stimulate endogenous acid production which would result in greater acid excretion leading to a lower urine pH and bicarbonate concentration. Previous studies have examined the effect ofin vivo administration of glucocorticoids on renal Na +/ H + antiporter activity studied in vitro (10,11 ). Administration of the same dose of subcutaneous dexamethasone as in the present study resulted in a 70% increase in Na+/H+ antiporter activity ( 10).…”
Section: Resultsmentioning
confidence: 59%
“…Previous studies have demonstrated that systemic administration of dexamethasone increases Na+ / H + antiporter activity, whereas adrenalectomy did not produce a decrease in antiporter activity (8,10,11 ). This effect of dexamethasone is caused by an increase in the Vmax of the Na+/H+ antiporter, with no change in the Km for sodium ( 11 ).…”
Section: Introductionmentioning
confidence: 96%
“…A similar mechanism appears to be responsible for renal proximal tubular sodium absorption, where administration of dexamethasone in rabbit for 1-2 days resulted in up to 2.5-fold increase in NHE3 transcript level, without an effect on NHE1 (10). As in ileum, glucocorticoids increased sodium absorption in renal brush border vesicles by increasing V max without altering the affinity for H ϩ or the Hill coefficient (36). Interestingly, incubation of isolated proximal tubules in dexamethasone for 3 h resulted in a 33% increase in NHE3 activity without a significant change in NHE3 or NHE1 transcript levels.…”
Section: Discussionmentioning
confidence: 90%